Reaction of Indian Gold Exchange Traded Funds to Covid-19 Cases and Fatalities - Ashima Gaba; Ravinder Kumar (Universitas Prasetiya Mulya, 2021)
Exchange Traded Funds (ETFs) are recently popularised new form of financial market instruments that provide benefit of both mutual funds and stocks. Present study investigated if there exists any difference between the average returns of selected Gold ETFs during COVID-19 era against pre COVID-19 era and subsequently analysed the long term and short term impact of new COVID-19 cases and fatalities on returns of Gold ETFs through Auto-regressive distributed lag (ARDL) model. It has been observed that in long term new COVID-19 cases had positive and significant impact on the returns of ETFs while new fatalities had significant negative impact on the returns of all the Gold ETFs except for BSLGOLD ETF. Short-run relationship between dependent and independent variables was in contrast to the long-term relationship. https://doi.org/10.21632/irjbs.14.3.187-198